2006
DOI: 10.1007/s10433-006-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

Are public care and services for older people targeted according to need? Applying the Behavioural Model on longitudinal data of a Swedish urban older population

Abstract: The objectives were to identify factors that predict the use of home help services and transition into institutional care and to study to what extent care services were targeted according to the individuals' needs. A further objective was to study whether people who had moved into institutional care facilities had received home help prior to institutionalisation. A community-dwelling sample (=502) aged 81-100 was twice interviewed and assessed with medical examinations. Their use of public elderly care between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 43 publications
5
62
1
1
Order By: Relevance
“…We know that the use of long-term care is very much dependent on functional impairment (e.g. Larsson et al 2006), and the number of bed days in hospital and use of health insurance services may not be perfect indicators of one's ability to perform the activities of daily living. Functional impairment is not connected to hospital admissions alone, and the use of health insurance services is not just connected to functional impairment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We know that the use of long-term care is very much dependent on functional impairment (e.g. Larsson et al 2006), and the number of bed days in hospital and use of health insurance services may not be perfect indicators of one's ability to perform the activities of daily living. Functional impairment is not connected to hospital admissions alone, and the use of health insurance services is not just connected to functional impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Municipal long-term care services are primarily allotted on the basis of an assessment of health and functional impairments (e.g. Stuart and Hansen 2006;Larsson et al 2006) and the use of these services is therefore connected to socio-economic factors. Research points to the fact that social status has a stronger effect than country of origin on self-rated and objective health (Albertsson et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most assistance is needed not only in instrumental activities of daily living (IADL) such as shopping and household chores, but also with basic hygiene (Grimmer et al 2004;Laukkanen et al 2001;Waters et al 2001). Divan et al (1997) showed that living alone predicted the use of home help, while low functional ability predicted the use of healthcare services (see also Larsson et al 2006;van Campen and van Gameren 2005;Kadushin 2004;van Campen and Woittiez 2003). Other factors found to be connected with the need for and use of services are female gender, selfrated health, comorbidity, recent inpatient care and feelings of loneliness (Bond et al 2006;Fortinsky et al 2004;Hellström et al 2004;Lee and Mills 2000;Crets 1996;Wallace and Hirst 1996;Rannhoff and Laake 1995).…”
Section: Introductionmentioning
confidence: 99%
“…According to Larsson et al (2006), dementia and depressive symptoms predicted the use of home help services (c.f. van Gameren and Woittiez 2005).…”
Section: Introductionmentioning
confidence: 99%